STRATEGI PEMASARAN DIGITAL UMKM DI BALI DALAM MENINGKATKAN PENJUALAN DI ERA NEW NORMAL - Gusti Ayu Putu Ardaba Kory; I Gede Sanica (ITB AAS INDONESIA Surakarta, 2022)
The outbreak of the Covid-19 pandemic has resulted in a decrease in revenue for various aspects of the business including in the culinary industry. The outbreak of the Covid-19 pandemic has resulted in a decrease in revenue for various aspects of the business including in the culinary industry. The challenge of marketing the digital world then demands the owner of Purnama Cake and Chocolate as a business that serves food products to be able to survive in the midst of the competition of digital culinary businesses. Based on the background obtained 2 problem formulations, namely: (1) How is the form of digital marketing applied by UMKM in Bali in increasing sales in the new normal era? As well as (2) How is the digital marketing strategy of UMKM in Bali in increasing sales in the new normal era?. The theory used in this study is digital marketing and SWOT analysis. This research uses a qualitative approach methodology. The material object of this study is Purnama Cake and Chocolate, while the formal object is digital marketing. This type of data collection is qualitative from primary and secondary data sources. Data collection techniques are observation or focused observation, in-depth interviews, combined with documentation studies and library research. The findings of the study are: (1) The form of digital marketing applied purnama cake and chocolate consists of 4C (co-creation, currency, communal activation, and convertation). (2) Purnama Cake and Chocolate's digital marketing strategy when viewed from SWOT analysis consists of Strength (strength), Weakness (weakness), Opportunity (Opportunity), and Threat (threat).